Study on the correlation between genetic polymorphism of angiotensin-converting enzyme (ACE) in Hainan Li Nationality and hypertension with atherosclerosis. (12th October 2011) - Mei-Ling, Yun; Yin, Zheng; Yu, Zeng; Tian-Fa, Li; Yong, Zhang; Shui-Jing, Jin; Zhen, Wang; Dai-Feng, Zhou; Wang-Wei, Cai
Abstract : Objective: To study the correlation between genetic polymorphism of angiotensin-converting enzyme (ACE) in Hainan Li Nationality and hypertension with atherosclerosis. Methods: ACE I/D gene polymorphisms were detected by PCR in 260 hypertension patients with atherosclerosis group and 276 healthy people (control) from Hainan Li nationality, and investigated the genotype frequencies and allele frequencies of DD, DI and II. Results: (1) In the hypertension with atherosclerosis group of Hainan Li nationality, the genotype frequencies of DD, DI and II were 15.0%, 27.3%, 47.7%, respectively, and the allele frequencies of D and I were 33.7% and 66.3%. In the control group, the genotype frequencies of DD, DI and II were 17.8%, 40.6% and 41.7%, respectively, and the allele frequencies of D and I were 38.0% and 62.0%, respectively. There were no significant differences both in the genotype frequencies of DD, DI and II, and in allele frequencies D and I between these two groups (p>0.05). (2) The logistic regression analysis showed that there were associations between TG (OR=2.14), ApoA (OR=360.39), SBP (OR=1.21), DBP (OR=1.08) and the hypertension with atherosclerosis group (p<0.05). The MIMT level in ACE DD subset were significant higher than in DI and II (p<0.05). Conclusions: The ACE DD genotype increases the susceptibility of carotid atherosclerosis. It is the risk factor in the hypertension with atherosclerosis group of Hainan Li nationality. It may be an early predictive factor in atherosclerosis.